Enhanced antineoplastic/therapeutic efficacy using 5-fluorouracil-loaded calcium phosphate nanoparticles - Mohiyuddin, Shanid; Naqvi, Saba; Packirisamy, Gopinath (Beilstein Journal of Nanotechnology, 2018)
In the past few decades, the successful theranostic application of nanomaterials in drug delivery systems has significantly improved the antineoplastic potency of conventional anticancer therapy. Several mechanistic advantages of nanomaterials, such as enhanced permeability, retention, and low toxicity, as well as surface engineering with targeting moieties, can be used as a tool in enhancing the therapeutic efficacy of current approaches. Inorganic calcium phosphate nanoparticles have the potential to increase the therapeutic potential of antiproliferative drugs due to their excellent loading efficiency, biodegradable nature and controlled-release behaviour. Herein, we report a novel system of 5-fluorouracil (5-FU)-loaded calcium phosphate nanoparticles (CaP@5-FU NPs) synthesized via a reverse micelle method. The formation of monodispersed, spherical, crystalline nanoparticles with an approximate diameter of 160–180 nm was confirmed by different methods. The physicochemical characterization of the synthesized CaP@5-FU NPs was done with transmission electron microscopy (TEM), dynamic light scattering (DLS), field emission scanning electron microscopy (FE-SEM), Fourier-transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD). The antineoplastic potential of the CaP@5-FU NPs against colorectal and lung cancer cells was reported. The CaP@5-FU NPs were found to inhibit half the population (IC50) of lung adenocarcinoma (A549) cells at 32 μg/mL and colorectal (HCT-15) cancer cells at 48.5 μg/mL treatment. The apoptotic induction of CaP@5-FU NPs was confirmed with acridine orange/ethidium bromide (AO/EB) staining and by examining the morphological changes with Hoechst and rhodamine B staining in a time-dependent manner. The apparent membrane bleb formation was observed in FE-SEM micrographs. The up-regulated proapoptotic and down-regulated antiapoptotic gene expressions were further confirmed with semiquantitative reverse transcriptase polymerase chain reaction (PCR). The increased intracellular reactive oxygen species (ROS) were quantified via flow cytometry upon CaP@5-FU NP treatment. Likewise, the cell cycle analysis was performed to confirm the enhanced apoptotic induction. Our study concludes that the calcium phosphate nanocarriers system, i.e. CaP@5-FU NPs, has higher antineoplastic potential as compared to 5-FU alone and can be used as an improved alternative to the antimitotic drug, which causes severe side effects when administrated alone.
Keywords: 5-FU; anticancer drug delivery; apoptosis; calcium phosphate nanoparticles; cell cycle; nanomedicine